Learning modal force: evidence from children’s production and input - Dieuleveut, Anouk; van Dooren, Annemarie; Cournane, Ailís; Hacquard, Valentine (Proceedings of the Amsterdam Colloquium, 2019)
This paper investigates when and how children figure out that possibility modals express possibility, and necessity modals, necessity. Given that necessary p entails possible p, what prevents children from hypothesizing possibility meanings for necessicity models? We argue that this entailment problem is not a psychological one. On the basis of a corpus study of the modal productions of 2-year-old English children and their mothers and two Human Simulation Paradigm experiments (Gillette et al. 1999), we show that children can use cues from the conversational context in which modals are used to learn force, and do not need to rely on negative environments, nor on a bias for necessity meanings